1978
DOI: 10.1002/cpt1978244448
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of norethindrone in women; II. Single‐dose kinetics

Abstract: In order to study the kinetics of norethindrone in women, we have administered single doses of 4 preparations of norethindrone (N) to Liverpool, England Department of Pharmacology and Therapeutics, University of LiverpoolNorethindrone ( 17a -ethinyl-I7 (3 -hydroxyestr-4-en-3-one) is a synthetic progestogen which is widely used both on its own and as a component of many combined contraceptive steroid preparations. Despite its widespread use, little is known of the relationship of blood concentrations of norethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Several pharmacokinetic studies have confirmed the biotransformation of lynestrenol to norethindrone in vivo and showed that this reaction is rapid and almost complete after oral administration of lynestrenol [4,6,7]. Although the pharmacokinetics of both lynestrenol and norethindrone have been intensively studied in humans [8][9][10][11], the involvement of cytochrome P450 (CYP) enzymes in the metabolism of lynestrenol and norethindrone have never been formally characterized. However, there is indirect evidence that CYP isoforms may contribute in the disposition of norethindrone.…”
Section: Introductionmentioning
confidence: 97%
“…Several pharmacokinetic studies have confirmed the biotransformation of lynestrenol to norethindrone in vivo and showed that this reaction is rapid and almost complete after oral administration of lynestrenol [4,6,7]. Although the pharmacokinetics of both lynestrenol and norethindrone have been intensively studied in humans [8][9][10][11], the involvement of cytochrome P450 (CYP) enzymes in the metabolism of lynestrenol and norethindrone have never been formally characterized. However, there is indirect evidence that CYP isoforms may contribute in the disposition of norethindrone.…”
Section: Introductionmentioning
confidence: 97%
“…Pharmacokinetics and bioavailability of norethindrone and ethinyl estradiol in human subjects have been characterized in many cases with the absolute bioavailability reported at ∼64 and 55% for norethindrone and ethinyl estradiol, respectively [7,8]. With the introduction of low dose combination of these two compounds, there is a growing concern about the possible interaction from co-administrated drugs, and a potential failure of contraception in women taking oral contraceptives or failure in women using this combination for non-contraceptive indications due to the altered circulating levels of norethindrone and ethinyl estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…These levels were selected because the lower doses used in these experiments corresponded closely to plasma concentrations of mestranol (Goldzieher, personal communication) and norethindrone 16 observed following their administration to human subjects. Equal volumes of ethanol (20 or 100 \i\), the solvent in which these hormones were dissolved, were added similarly to dishes containing 10% serum alone.…”
Section: Growth Experimentsmentioning
confidence: 99%